Something like fate - Colasanti, Susane (New York : Viking, 2010)
Lani and Jason, who is her best friend's boyfriend, fall in love, causing Lani tremendous anguish and guilt.
Young Adult.
Young Adult
Keywords: Friendship -- Juvenile fiction; Guilt -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Guilt -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction; Friendship -- Fiction; Guilt -- Fiction; Interpersonal relations -- Fiction; School stories